The Effects of Sensorimotor Training Programs on Static Single Leg Balance in Soccer Players with Chronic Ankle Sprain - Madee, Nitiporn; Artpui, Thanyamai; Mingkhuan, Yukolthorn; Krityakiarana, Warin (Journal of Health Science of Thailand, 2017)
Ankle sprain in athletic is resulting in reduce ability of balance and ankle control. The exercise program, which is a part of physical therapy treatment, has been proved in improving balance and ankle control in athletes with ankle sprain. Our sensorimotor training program has been proved that increased the dynamic balance ankle abilities. Therefore, the purpose of this study was to evaluate the effects of our sensorimotor training programs on static balance in soccer players with chronic ankle sprain. Thirty subjects were randomly separated into two groups. The experimental group (n=15) received standard exercise (elastic tube exercise) combined with developing sensorimotor training programs. The control group (n=15) performed only standard exercise. Balance control of unilateral stance (effected side) was compared between before and after training by using a Prosmart balance version 8®. The parameter was mean center of gravity (COG) sway velocity. Mean center of gravity sway velocity values were analyzed by using a Two-way mix ANOVA. It was found that there were no significant differences in mean center of gravity sway velocity between the control and the experimental groups either before or after the training program. However, there were significant difference within group between before and after exercise. From our study, the combined training exercise was not affecting the balance control in chronic ankle sprain. However, it confirmed the positive results of sensorimotor training program in physical therapy for athletics with chronic ankle sprain.